Nullity, yes; revocation, no: safeguarding legal certainty - León Pinedo, Silvia (2022)
In tax procedural law, when a resolutive body opts for the revocation and not for the nullity of an administrative act, the public interest is harmed, undermining the legal certainty, and generating a greater litigation at the cost of the taxpayer, both on time and money. This study shows that, on taxation matters, the consequences of both categories are completely different, and it is essential that nullity be declared when the existence of substantial defects is proved. The resolutions of the Peruvian Taxation Tribunal are evaluated to ponder which is the line followed by the collegiate, finding that not in all the cases the referred categories are respected, which results in lawsuits of SUNAT before the Peruvian Judiciary.